Impact Of Work Life Balance On Employee Job Satisfaction Among Bank Employees In Bangalore District - N, Dr. Abhinandan (The journal of contemporary issues in business and government, 2021)
The present study of work life balance in banking sector covered the employees from public, private and co-operative banks having their branches in Bangalore district. The study covered employees at each hierarchical levels of the branches like branch managers, officers from various departments and clerks and sub staff employed. An in depth study is carried out to study life satisfaction and job satisfaction among the bank employees. This is an attempt to analyse work life balance and related issues. The required data for analysis was generated through primary and as well as secondary sources. Data input was being of 440 bank employees and having different variables under study, its analysis was done using IBM SPSS Statistics 20.0 the statistical tools applied for the analysis of primary data are ANOVA. This study reveals the association between life satisfaction and work life balance, and the association between job satisfaction and work life balance. The present study provides recommendations that a practical implementation of the suggestions like facilitating mentoring, yoga, workshop etc., can be initiated and results may be evaluated.